Pengaruh Kombinasi Kompos Kulit Kopi dan Pupuk NPK Terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) di Mekarbuana Kabupaten Karawang - Prayoga, Denda; Muharam, Muharam; Muhamad B, Fawzy (UNIVERSITAS LABUHANBATU, 2023)
The purpose of this study is tostudying and obtaining a combination of coffee skin compost and npk fertiliser that is able to provide the highest results on the growth and yield of cayenne pepper plants (Capsicum frutescens L). The experimental design was design used is a single-factor Randomised Group Design (RGD) consisting of 5 treatments in 5 replications consisting K0 (NPK 500 kg/ha); K1 (Coffee Peel Compost 7 tonnes/ha + NPK 450 kg/ha); K2 (Coffee Peel Compost 8 tonnes/ha + NPK 400 kg/ha); K3 (Coffee Peel Compost 9 tonnes/ha + NPK 350 kg/ha); K4 (Coffee Peel Compost 10 tonnes/ha + NPK 300 kg/ha).The data obtainedwere analyzed by variance, and if the results was significant, then to find out the best treatment continued with the DMRT (Duncan Multiple Range Test) further test at the 5% level.Theresultsshowedthe provision of various combinations of coffee skin compost and npk fertiliser gave a significant effect on the growth of stem diameter and number of leaves but had no significant effect on plant height. However, it has a significant effect on the number of fruits per plant, fruit weight per plant and fruit weight per bed. The K3 treatment (combination of 9 tonnes/ha coffee skin compost + 350 kg/ha NPK) was able to provide the best growth on stem diameter 28 dap, number of leaves 21 dap and 28 dap. Meanwhile, Treatment K4 (coffee skin compost 10 tonnes/ha + NPK 300 kg/ha) was able to give the best results on the number of fruits per plant and fruit weight per plant. While treatment K1 (coffee skin compost 7 tonnes/ha + NPK 450 kg/ha) obtained the best results on the average weight of fruit per bed of 1,134.38 grams/bed or 2.26 tonnes/ha.Â Keywords:Cayenne Pepper, Coffee Peel Compost, NPK Fertilizer